Geophysical surveys of stratigraphically complex Island California sites : new implications for household archaeology - Arnold, Jeanne E.
Ground-ponotrating radar and other geophysical techniques are known to produce useful data when deposits are crisply structured, as in the case of sub-surface masonry walls or large ditches. New studies of Californian coastal sites find the methods are effective in tracing the less sharp distinctions that define clay and sand house floors within these large and dense hunter-gatherer middens.